Drug utilization and medical expenses in psoriasis treatment at a dermatology hospital in Vietnam, 20192021 - Hung, N. P.; Huong, V. T. M.; Kieu, D. T. V.; Quan, L. T.; Minh, N. T. T.; Thuy, N. P. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Psoriasis is a persistent, chronic, inflammatory cutaneous disorder that recurs frequently and has negative impacts on the living quality of sufferers.Methods. Data from the Inpatient and Outpatient Department medical records at Can Tho dermatology hospital were used to generate a descriptive statistics report on medicines and medical costs for psoriasis therapy in 2019-2021.Results. The average number of prescription medications varied annually, averaging roughly 0.62±85.4% per prescription. Corticosteroids and calcipotriol were the most commonly recommended drugs for psoriasis. Antihistamines were the most often used medication, with over 12,000 instances among the 28,397 individuals studied. The peak in average per-treatment expenses occurred in 2021 when they fluctuated between US $120 and US $160. In contrast, examination expenses were the most costly, ranging from US $93-$107.Conclusion. The bulk of psoriasis therapy treatments were topical agents, whose quantities rose progressively. Direct examination expenses accounted for the greatest proportion.